The Analysis of Legal Evidence Case on Criminal Employment through Electronic Systems - Somaerin Saputra; Anis Mashdurohatun; Latifah Hanim (Law Development Journal, 2022)
The purpose of this study is to find out and analyze legal evidence related to criminal acts of embezzlement through an electronic system. To find out and analyze the basis of judges' considerations in making decisions on criminal acts of embezzlement through an electronic system. The method used by the researcher is empirical juridical approach and the specifications in this study include descriptive analysis. As for the sources and types of data in this study, secondary data were obtained from literature studies. Data analyzed qualitatively. Based on the results of the study that Legal Evidence Regarding the Crime of Embezzlement Through Electronic Systems that the power of proving electronic evidence in criminal procedural law, the strength of all evidence is essentially the same, no one exceeds the other. Evidence in criminal procedural law does not recognize hierarchy. It's just that there are provisions that require the connection between one evidence and another. Therefore, in criminal procedural law there is complementary evidence.